👤

1. The square root of the sum of a number and 3 is equal to the sum of the number and 1.

a. What is the mathematical equation that represents the statement?

b. What is the number?​


Sagot :

Answer:

[tex]\sqrt{x+3} = x+1[/tex]

x=1

Step-by-step explanation:

Answer:

a. Mathematical equation:

[tex] \sqrt{x + 3} = x + 1[/tex]

b. The number is either -2 or 1.

Solution:

For question b

[tex] \sqrt{x + 3} = x + 1 \\ {( \sqrt{x + 3}) }^{2} = {(x + 1)}^{2} \\ x + 3 = {x}^{2} + 2x + 1 \\ {x}^{2} + x - 2 = 0 \\ (x + 2)(x - 1) = 0 \\ x = - 2 \\ x = 1[/tex]

Checking:

If x = -2

[tex] \sqrt{x + 3} = x + 1 \\ \sqrt{ - 2 + 3} = - 2 + 1 \\ \sqrt{1} = - 1 \\ - 1 = - 1[/tex]

If x = 1

[tex] \sqrt{x + 3} = x + 1 \\ \sqrt{1 + 3} = 1 + 1 \\ \sqrt{4} = 2 \\ 2 = 2[/tex]

#CarryOnLearning

>_<